Interactive effects of elevated temperature and drought on plant carbon metabolism: A meta‐analysis. Issue 10 (24th February 2023) - Wang, Zhaoguo; Wang, Chuankuan
Abstract: Elevated temperature ( T e ) and drought often co‐occur and interactively affect plant carbon (C) metabolism and thus the ecosystem C cycling; however, the magnitude of their interaction is unclear, making the projection of global change impacts challenging. Here, we compiled 107 journal articles in which temperature and water availability were jointly manipulated, and we performed a meta‐analysis of interactive effects of T e and drought on leaf photosynthesis ( A growth ) and respiration ( R growth ) at growth temperature, nonstructural carbohydrates and biomass of plants, and their dependencies on experimental and biological moderators (e.g., treatment intensity, plant functional type). Our results showed that, overall, there was no significant interaction of T e and drought on A growth . T e accelerated R growth under well‐watered conditions rather than under drought conditions. The T e  × drought interaction on leaf soluble sugar and starch concentrations were neutral and negative, respectively. The effect of T e and drought on plant biomass displayed a negative interaction, with T e deteriorating the drought impacts. Drought induced an increase in root to shoot ratio at ambient temperature but not at T e . The magnitudes of T e and drought negatively modulated the T e  × drought interactions on A growth . Root biomass of woody plants was more vulnerable to drought than that of herbaceous plants at ambient temperature, but this difference diminished at T e . Perennial herbs exhibited a stronger amplifying effect of T e on plant biomass in response to drought than did annual herbs. T e exacerbated the responses of A growth and stomatal conductance to drought for evergreen broadleaf trees rather than for deciduous broadleaf and evergreen coniferous trees. A negative T e  × drought interaction on plant biomass was observed on species‐level rather than on community‐level. Collectively, our findings provide a mechanistic understanding of the interactive effects of T e and drought on plant C metabolism, which would improve the prediction of climate change impacts. Abstract : We performed a meta‐analysis of interactive effects of elevated temperature and drought on leaf photosynthesis and respiration, nonstructural carbohydrates and biomass of plants, and their dependencies on experimental and biological moderators (e.g., treatment intensity, plant functional type). Our results showed that there was no significant interaction of elevated temperature and drought on photosynthesis, stomatal conductance and leaf soluble sugar concentration but a negative interaction on leaf starch concentration, plant biomass and root to shoot ratio. The interactive effects varied with the magnitude of elevated temperature, drought severity, plant growth form, species longevity, tree functional type, and ecological level.